Frontal sinusitis associated with orbital decompression for Graves' orbitopathy. Issue 6 (December 2020) - Tatehara, Shun; Inokuchi, Go; Takeda, Hiroko; Kuroki, Shunsuke; Fujio, Hisami; Azumi, Atsushi; Nibu, Ken-ichi
Abstract: Orbital decompression (OD) for Graves' orbitopathy usually includes removal of orbital medial wall. While OD occasionally cause or worsen chronic sinusitis because of the obstructed sinus drainage by prolapsed orbital fat, to date few reports have been published on the management or prevention of sinusitis associated with OD. Here, we present two patients (three sides) with newly developed and one patient (one side) with worsening obstructive frontal sinusitis following OD. These three patients had OD including the removal of the superior attachment of uncinated process to lamina papyracea. Endoscopic modified Lothrop procedure (EMLP) was useful to relieve symptoms and keep an enough access to frontal sinuses for all cases. We also performed EMLP for another two patients (four sides) with pre-existing sinusitis before OD. Worsening of sinusitis could be avoided by EMLP before OD. EMLP was useful approach for both treatment and prevention of sinusitis related to OD. The superior attachment site of uncinated process and the pattern of frontal sinus drainage might predict the occurrence of obstructive frontal sinusitis following OD.